2016
DOI: 10.1016/j.jadohealth.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Teen Dating Violence Typologies

Abstract: Purpose The goal of the present research was to identify distinct latent classes of adolescents that commit teen dating violence (TDV) and assess differences on demographic, behavioral, and attitudinal correlates. Methods Boys and girls (N = 1,149; Mage = 14.3; Grades 6–12) with a history of violence exposure completed surveys assessing six indices of TDV in the preceding 3 months. Indices of TDV included controlling behaviors, psychological TDV, physical TDV, sexual TDV, fear/intimidation, and injury. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 38 publications
9
51
1
11
Order By: Relevance
“…The finding that the psychologically aggressive victims latent class (24% of girls; 34% of boy) was more prevalent than the multiform aggressive victims latent class (11% of girls; 10% of boys) is also consistent with previous research with general population samples that has found that, among youth who are involved in dating violence, the most typical pattern of behavior is characterized by involvement in psychological abuse only (Choi and Temple 2016; Diaz-Aguado and Martinez 2015; Goncy et al 2016; Haynie et al 2013; Reidy et al 2016). Although we did not include a specific measure assessing acceptance of psychological dating violence in the current study, this pattern of findings may reflect more permissive attitudes toward the use of psychological abuse against dating partners than toward the use of physical and sexual abuse.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that the psychologically aggressive victims latent class (24% of girls; 34% of boy) was more prevalent than the multiform aggressive victims latent class (11% of girls; 10% of boys) is also consistent with previous research with general population samples that has found that, among youth who are involved in dating violence, the most typical pattern of behavior is characterized by involvement in psychological abuse only (Choi and Temple 2016; Diaz-Aguado and Martinez 2015; Goncy et al 2016; Haynie et al 2013; Reidy et al 2016). Although we did not include a specific measure assessing acceptance of psychological dating violence in the current study, this pattern of findings may reflect more permissive attitudes toward the use of psychological abuse against dating partners than toward the use of physical and sexual abuse.…”
Section: Discussionsupporting
confidence: 90%
“…Further, based on research suggesting that, compared to girls, boys are more likely to report sexual violence perpetration and less likely to report sexual violence victimization we expected that, among boys, multiform aggressive victims would be characterized by high probabilities of endorsing all dating violence indicators except sexual violence victimization whereas, for girls, this class would be characterized by high probabilities of endorsing all indicators except for sexual violence perpetration. The expectation that classes would be distinguished by the form of dating violence (i.e., psychological only vs. multiple forms of dating violence) is also supported by research that has identified dating violence profiles using measures of victimization only (Choi and Temple 2016) or perpetration only (Diaz-Aguado and Martinez 2015; Reidy et al 2016). The current study expands on this body of literature by examining patterns of dating violence involvement in a sample of Latino youth, by determining whether the nature of these patterns varies by sex, and by including measures of psychological, physical, and sexual victimization and perpetration as indicators of latent class membership.…”
Section: The Current Studymentioning
confidence: 98%
“…Many scholars have noted the importance of examining IPV as a heterogeneous phenomenon to better understand the risks associated with different types of IPV; to more accurately assess for IPV; and to match people with the most appropriate interventions (Capaldi & Kim, 2007; Cavanaugh & Gelles, 2005; Kelly & Johnson, 2008). Researchers have begun to focus on the heterogeneity of IPV specific to adolescent couples (Paradis, Hébert, & Fernet, 2015; Reidy et al, 2016). We examine four profiles of IPV in the relationships of expectant adolescent couples: no IPV, female IPV victim only, male IPV victim only, and mutual IPV.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used latent class analysis to identify homogeneous subgroups of individuals who perpetrate IPV (e.g., Choi, Weston, & Temple, ; Haynie et al, ; Reidy et al, ). Although prior studies used different measures of IPV, examined different correlates of group membership, and used different samples (Reidy et al () used a high risk sample, and Choi et al () and Haynie et al (), used community samples of adolescents), in each, homogenous groups of individuals who engaged in distinct forms of psychological and/or physical IPV were identified. Moreover, classes emerged that consisted of no IPV, a high likelihood of psychological IPV without physical IPV, and a class that consisted of multiple forms of IPV (e.g., psychological, physical).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research, albeit limited, also suggests that personality characteristics may be important for understanding the co‐occurrence and severity of psychological and physical IPV (Caiozzo, Houston, & Grych, ; Reuter, Sharp, Temple, & Babcock, ). Characteristics related to general aggressive tendencies, such as callous‐unemotional traits (Caiozzo et al, ), proactive and reactive aggression (Reidy et al, ), and impulsive outbursts of intense anger associated with borderline personality disorder (Reuter et al, ), have each been linked to IPV. It remains unclear, however, whether these personality traits represent distinct or shared covariates among IPV types.…”
Section: Introductionmentioning
confidence: 99%